Development and evaluation of a concise food list for use in a web-based 24-h dietary recall tool - Katie Evans; Áine Hennessy; Janette Walton; Claire Timon; Eileen Gibney; Albert Flynn (Journal of Nutritional Science, 2017)
Foodbook24 is a self-administered web-based 24-h dietary recall tool developed to assess food and nutrient intakes of Irish adults. This paper describes the first step undertaken in developing Foodbook24 which was to limit participant burden by establishing a concise list of food items for inclusion in the tool. The aim of the present study was to evaluate whether using a concise food list (as opposed to an extensive list) with generic composition data would influence the estimates of nutrient intakes in a nationally representative sample of Irish adults. A 2319-item food list generated from the Irish National Adult Nutrition Survey (NANS) (2008–2010) (n 1500) was used as the basis for a shortened food list for integration into the tool. Foods similar in nutritional composition were recoded with a generic type food code to produce a concise list of 751 food codes. The concise food list was applied to the NANS food consumption dataset and intake estimates of thirty-five nutrients were compared with estimates derived using the original extensive list. Small differences in nutrient intakes (<6 %) with limited effect size (Cohen's d < 0·1) were observed between estimates from both food lists. The concise food list showed strong positive correlations (r s 0·9–1·0, n 1500, P < 0·001) and a high level of agreement with the extensive list (80–97 % of nutrient intakes classified into the same tertile; >90% of intakes similarly categorised according to dietary reference values). This indicates that a concise food list is suitable for use in a web-based 24-h dietary recall tool for Irish adults.